Innovation performance growth among small and medium sized firms in Malaysia - Abraham, Abasiti Victor; Rashidah, Mohamad Ibrahim; Wan Abd Aziz, Wan Mohd Amin (2016)
Innovation is considered as a vital tool that help to promote opportunities of new business growth and market. However, there has been an improved remarkable increase in business and organisation expansion as a result of innovation implementation. Due to the high level of competition amongst SME's in Malaysia and globally, it is essentials for organisation to enhance their strategic innovation to suit their organisation culture, employees and leadership styles so as to enhanced and maintain their flow of performance growth. Innovation is important to organisation and which is seems as one of the strategies that positioned organisation at the high pace of performance. Innovation is defined as a natural renewable source accessible to all restricted only by human effort. It is also affirmed that innovation create a positive impact of the organisation capability. Considering SME's, it has been identified that most SME's lack innovation as a results of information acquisition and interpretation that leads to their low performance effectively. In this research proposal, I will focus on the innovation performance growth of SME's in Malaysia and which will be discussed on their background of study. problem statement. research question, objectives and significant of study. in order to boast the performance growth of SME's in Malaysia.